The "Just War" Theory: Application to United States and Israeli Militarism - Maguire, Daniel C. (Social justice, 2010)
The article discusses the "just war theory" in international relations with a focus on the militarism of the U.S. and Israel. A brief overview of the history of wars is presented. The characteristics of a "just war" are discussed which include a just cause, a war declaration by a legitimate government, and the principle of double effect in negative outcomes of wars. It is suggested that corporate interests and lobbying interests are deemed more important than social justice during the application of just wars.